Cultural Haunting: The Translation of Culturally Embedded Horror Concepts in Indonesian Movie Synopses - Ikke Dewi Pratama; Suryo Ediyono (Universitas Sebelas Maret, 2026)
Indonesian horror movies are often characterized by their deep engagement with culturally specific concepts forming the narratives. When these films are introduced to international audiences through streaming platforms, the synopses, which are intended to be brief and persuasive, must balance clarity with cultural integrity. This study investigates two key issues: (1) the translation techniques employed to render culturally embedded horror-related concepts from Indonesian into English, and (2) the extent to which these techniques influence the representation of Indonesian cultural identity in the translated synopses. The data are 43 culturally embedded horror concepts and their English translated versions taken from Netflix. Using four stages of ethnography approach as the data analysis technique, results revealed that the translation techniques used are: literal translation, modulation, generalization, adaptation, borrowing, and established equivalence. Meanwhile, the impacts of the translation techniques towards the representation of Indonesian culture are categorized into: preservation, transformation, and reduction. This study contributes theoretically to the frameworks of translator’s decisions on cultural visibility. Practically, it also gives insights on the possible problems and solutions of rendering culturally specific concepts in short, high-stakes texts aimed at global viewers. Keywords: culture, movie, synopsis, techniques, translation